ANALISE ANTIGENICA DE PROTEASES DE DIFERENTES CEPAS DE TRICHOMONAS VAGINALIS ISOLADAS DE PACIENTES DA REGIAO DE ARARAQUARA, SP, BRASIL - De Freitas, A. C. [UNESP]; Teixeira, D. C. [UNESP]; Barretto-Cicarelli, R. M. [UNESP] (My University, 1995)
Trichomonas vaginalis is the flagellate that causes trichomonadiasis, a sexually transmitted disease. Immunological methods have been proposed for the study of antigenic characterization using strains isolated from different patients. This work compares protease profiles from the different strains using gelatin containing polyacrylamide gels to analyse the protease activity. High molecular weight proteases (20 to 100 kDa) were found on gels showing quantitative differences. Human IgG antiproteases were detected by immunoblotting using the same extracts. These proteases could be related with T. vaginalis pathogenesis.
Antigenic analysis from proteases of different strains of Trichomonas vaginalis isolated from Araraquara (SP, Brazil) region patients
Keywords: gelatin-SDS-PAGE; immunoblotting; proteases; Trichomonas vaginalis; proteinase; brazil; controlled study; human; nonhuman; polyacrylamide gel electrophoresis; trichomonas vaginalis; trichomoniasis